Multinationalism, Japanese Style : the Political Economy of Outward Dependency. - Ozawa, Terutomo (Princeton legacy library., 2014)
Analyzing the motivating forces behind the trend toward Japanese direct overseas production, this work examines the appreciation of the yen, rising labor and energy costs, environmental decay, shortages of industrial sites, and critical dependence on overseas resources as factors in prompting Japanese firms to transfer production facilities abroad. Originally published in 1982. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These pa.